ANALISA KESTABILAN GENETIK PISANG KEPOK ‘UNTI SAYANG’ HASIL MIKROPROGASI DENGAN MARKA RAPD DAN ISSR - Yuyu Suryasari Poerba; Maria Imelda; Diyah Martanti (BERITA BIOLOGI, 2012)
Random Amplified Polymorphic DNA (RAPD) and Inter-Simple Sequence Repeats (ISSR) markers were used to evaluate the genetic stability of micropropagated plants of ‘Pisang Kepok Unti Sayang’ at various stage of in vitro sub-cultures and in vivo plant material.All RAPD and ISSR profiles from micropropagated plants were monomorphic and similar to those of field grown control plants until stage tenth of sub cultures (V1S10). No variation was detected within the micropropagated plants, except for C12 (V1S44),G7 (V1S48 ), I11 and I12 (V1S10).RAPD and ISSR marker were both could be used to test the genetic stability of micropropagated bananas using the developed protocol.